Controversial Role of Kisspeptins/KiSS-1R Signaling System in Tumor Development - Fratangelo, Federica; Carriero, Maria Vincenza; Motti, Maria Letizia (Frontiers in Endocrinology, 2018)
KiSS-1 was first described as a metastasis suppressor gene in malignant melanoma. KiSS-1 encodes a 145 amino-acid residue peptide that is further processed, producing the 54 amino acid metastin and shorter peptides collectively named kisspeptins, (KPs). KPs bind and activate KiSS-1R (GPR54). Although the Kisspeptin system has been extensively studied for its role in endocrinology of reproductive axis in mammalian, its role in cancer is still controversial. Experimental evidences show that Kisspeptin system exerts an anti-metastatic effect by the regulation of cellular migration and invasion in several cancer types. However, the role of KPs/KiSS-1R is very complex. Genomic studies suggest that KiSS-1/KiSS-1R expression might be different in the various stages of tumor development. Furthermore, overexpression of KiSS-1R has been reported to elicit drug resistance in triple negative breast cancer (TNBC). In this review we focused on multiple functions exerted by the Kisspeptins/KiSS-1R system in regulating tumor progression.